Liosina paradoxa sponge ethanol extract's antioxidant activity test taken from Poopoh Village's Southern Beach - Polakitan, Odelia Amabel; Yudistita, Adithya (UNIVERSITAS SAM RATULANGI, 2024)
Liosina paradoxa sponge is one of the Indonesian marine biota that contains compounds that have strong bioactivity. This study was conducted with the intention to determine the antioxidant activity contained in Liosina paradoxa sponge. This research is a laboratory experimental research where this test uses DPPH method. The results showed that Liosina paradoxa sponge has antioxidant activity with the highest concentration having a percentage reaching 75%.